Answer:
12
Step-by-step explanation:
A midpoint of a line means that each segment connecting from the midpoint to an end is equal. For this problem, this means that AB = BC, as B is the midpoint, and A and B are the ends. Therefore, we can say that:
AB = BC
2x + 6 = 5x - 3
add 3 to both sides
2x + 9 = 5x
subtract 2x from both sides
9 = 3x
divide both sides by 3
3 = x
Plugging 3=x into AB, this means that 2(3) + 6 = AB = 12
Answer:
1
Step-by-step explanation:
Answer:
2x+7
Step-by-step explanation:
To Simplify an Expression , we combine Like-Terms
So for our Question , we have Terms with x and Constant Term
Combine Terms with x : 5x-2x-x=2x
Constant Term : 7
Then 5x-2x+7-x = 2x+7
Sorry, but I generally respond to only 1 or 2 problems when someone gives me a long list of homework. It would take you just a little longer to post one problem at a time.
75 5 -375
Let's look at #5: 75 / (-1/5) is the same as -------- = 75 * ------ = --------- -1 -1 1
---
5
and this is equivalent to -375 (answer to #5)